pls solved this question
Attachments:
![](https://hi-static.z-dn.net/files/d2d/0512bf147d45edc86c813219f69ecdd2.jpg)
Answers
Answered by
0
Please see the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d09/7f403baf2c3329fe0d4cbb456a6bdd38.jpg)
Answered by
0
Answer:
Step-by-step explanation:
Sin ⁸ x –Cos ⁸ x = ( 1 – 2 Cos²x) ( 1 – 2 Sin²x Cos²x)
LHS
Sin ⁸ x –Cos ⁸ x
= ( Sin⁴ x ) ² – (cos⁴ x) ²
= ( Sin⁴ x - Cos⁴ x ) ( Sin⁴ x + Cos⁴ x )
= ( Sin² x - Cos² x ) ( Sin² x + Cos² x ) ( Sin⁴ x + Cos⁴ x )
= ( Sin² x - Cos² x )(1) ( Sin⁴ x + Cos⁴ x ) as Sin² x + Cos² x=1
writing Sin² x= 1-Cos² x & adding and subtracting 2 Sin² xCos² x in second factor
=(1 - Cos² x -Cos² x )( Sin⁴ x + Cos⁴ x+ 2 Sin² xCos² x - 2 Sin² xCos² x)
= (1 -2 Cos² x) [( Sin² x + Cos² x )² - 2 Sin² xCos² x]
= (1 -2 Cos² x) [( 1)² - 2 Sin² xCos² x] as Sin² x + Cos² x=1
= ( 1 – 2 Cos²x) ( 1 – 2 Sin²x Cos²x)
Similar questions